Empirical research on the influence of corporate digitalization on green innovation - Li, Jinke; Wang, Le; Nutakor, Felix (Frontiers in Environmental Science, 2023)
The link between corporate digitization and green innovation is now receiving attention from all spheres of life in light of the rapidly developing digital economy and the goal of sustainable development. This study explores how corporate digitalization affects green innovation, its mediating mechanism, and moderating effects by integrating resource-based theory, attention-based view, and institutional theory. We utilize the panel data of Chinese Shanghai and Shenzhen A-share manufacturing corporation data from 2011 to 2020 as samples and use the fixed effect model in linear regression of panel data for regression analysis. Research findings: 1) corporate digitalization fosters not only green innovation directly but also promotes green innovation by enhancing human capital. 2) Executive team environmental attention encourages the beneficial correlation between human capital and green innovation. 3) Media attention promotes the favorable relationship between corporate digitalization and green innovation. 4) Heterogeneity analysis revealed that the corporate digitalization effect on green innovation is more significant when firms are more prominent in high-tech industries. The findings encourage corporations to strengthen their digital strategy, infrastructure, and applications. In addition, they can also inspire green innovation to enable companies to develop sustainably.